Phenomenology and Transcendence: On Openness and Metaphysics in Husserl and Heidegger - Cassara, Bruno (Religions, 2022)
In this paper I examine the relationship between phenomenology and metaphysics by reassessing the relationship between phenomenological and metaphysical transcendence. More specifically, I examine the notion of phenomenological transcendence in Husserl and the early Heidegger: Husserl defines transcendence primarily as the mode of givenness of phenomena that do not appear all at once, but must be given in partial profiles; Heidegger defines transcendence primarily as Dasein’s capacity to go beyond entities toward being. I argue that these divergent understandings of phenomenological transcendence have resulted in a significant difference in reception among French phenomenologists of religion. These thinkers assert that phenomenology, when properly conceived and utilized, can make room for the divine and its revelation, i.e., for a metaphysical transcendence. I further argue that these thinkers prefer Heidegger’s phenomenology to Husserl’s because they understand Heidegger’s transcendence as the subject’s openness to being, while they understand Husserl’s transcendence as a limit, as the inability to capture worldly objects. I take up Jean-Luc Marion’s phenomenology of givenness as a “case study” to illustrate this point. Finally, I argue that this preference for Heidegger over Husserl is misplaced and should be reversed. A close reading of Heidegger’s Phenomenology of Religious Life shows that Dasein is confined to its own possibilities and cannot be open to a relationship with the divine. By contrast, Husserl’s phenomenology provides the radical openness necessary to welcome revelation. While Husserl cannot envision a “worldly God,” the structures of horizonality and temporality characterize a subject capable of an authentic openness to revelation.